Frictions and taxpayer responses: Evidence from bunching at personal tax thresholds - Stuart Adam; James Browne; David Phillips; Barra Roantree (Institute for Fiscal Studies (IFS), 2017)
We investigate bunching at personal tax thresholds over a 40-year period. At kinks, where the marginal tax rate rises, we find bunching among company owner-managers and the self-employed, but not those with only employment income. Notches, where the average rate rises, provide compelling evidence that this is because most employees face substantial frictions: fewer than a quarter bunch even where doing so would increase consumption and leisure. We develop a new approach for identifying selection in who responds and for decomposing responses into hours and wage components. We find that employees who bunch at notches are higher-hours, lower-wage, part-time workers.
Keywords: H20; H24; J22; 330; Behavioural response; income tax; social security contributions; optimisation frictions; elasticity of taxable income